Qihuang needle therapy in senile cervical spondylotic radiculopathy - Yang, Juan; Huang, Hongfang; Shi, Jinshan; He, Cheng; Zhang, Kun; Chen, Zhenhu; Zeng, Rui; Liu, Jia (Frontiers in Aging Neuroscience, 2023)
Background Neurogenic cervical spondylosis [cervical spondylotic radiculopathy (CSR)] accounts for ~50–60% of all types of cervical spondylosis, and its incidence is the highest among all types of cervical spondylosis. Objective The present study aimed to investigate the clinical efficacy of the Qihuang needle in the treatment of senile cervical radiculopathy. Methods A total of 55 elderly patients with neurogenic cervical spondylosis were randomly divided into the general acupuncture group (27 cases) and the Qihuang acupuncture group (28 cases). The treatment given to these patients lasted for three sessions. The VAS scores and the Tanaka Yasuhisa Scale scores were compared before the treatment, after the first treatment, after the first session, and at the end of the session. Results The basic data of the two groups before the treatment showed no difference. The VAS scores in the mackerel acupuncture group decreased significantly, whereas in the Tanaka Kangjiu Scale scores, the efficiency rates of the first and second courses of treatment increased significantly. Conclusion The Qihuang needle therapy is recommended for the treatment of cervical spondylosis of the nerve root type. The said therapy is characterized by selection of fewer acupoints, a quick operation time, and no needle retention.